Castle Café / Nurul 'Aqilah Sariman ... [et al.] - Sariman, Nurul 'Aqilah; Mohamed Shaihan, Siti Nor Syahira; Mohd Sahit, Syamsulina; Alias, Nurain Solehah (2021)
The task of this study was to find out how to manage one’s own business, and how changes to this business were made. In addition, the task given is to identify customer segments, value propositions, channels, customer relationships, revenue streams, key activities, key sources, key partnerships, and also the cost structure found in this business namely Castle Café. The management and change of this business is done to find out how the whole business is run. The business involves a restaurant business that sells western side dishes and dishes to customers directly as well as online. In addition, the problems found in this type of restaurant business are also studied one by one to be changed for the better. The management of this Cafe can also be seen in terms of the prices placed on each food menu, as well as the quality of online management to customers and consumers. The financial management in this cafe is also handled and changed to see the sales target to be achieved.